Grönstrukturen i Örnsköldsvik - Olofsson, Sofia (2009)
During the autumn of 2008 I obtained office experience by working at the local government of Örnsköldsvik. I started working on the district green plan of the green structure and that led to the work of this exam paper. The purpose of this exam paper has been to define some standpoints for the green structure of the local government district of Örnsköldsvik. I have used both a larger and a smaller scale to obtain a wide a perspective as possible of the green structure. The larger scale gives an overall view of the whole municipality while the smaller scale is found in the study of the two local areas Centrum and Domsjö.